(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This scientific article provides a comprehensive analysis of the role, significance, and development prospects of artificial intelligence (AI) technologies in the modern education system. Within the context of digital education, the opportunities for individualized instruction based on AI, automated knowledge assessment, monitoring of the educational process, and optimization of pedagogical activity are examined. Furthermore, the challenges arising during the implementation of AI technologies in the education system and scientifically grounded solutions to overcome them are discussed.